Hypsodont Crowns as Additional Roots: A New Explanation for Hypsodonty - Solounias, Nikos; Danowitz, Melinda; Buttar, Irvind; Coopee, Zachary (Frontiers in Ecology and Evolution, 2019)
The hypsodont crown of Equus and of other hypsodont ungulates has two functions: It is extra crown in the alveolus which erupts and becomes a functional crown that enables the horse to live longer and feed on abrasive foods and the grit. The second functional aspect is that the crown, while it is in the alveolus, acts as a root to support the high stresses during mastication. In general, roots do not increase is size during the evolution when the tooth crown increases. Delayed development of the true roots is a heterochrony phenomenon and it is possibly dynamically interactive with the forces applied on the crown. Thus, when the crown is worn a lot as in old age, the mastication forces acting on it are very strong. This is an interesting phenomenon and reinforces our hypothesis of the second functional difference that the young tooth’s crown embedded in the alveolus acts as a supporting root. The Equus hypsodont tooth has been represented by a class I lever. That is, the fulcrum is in the middle: the effort is applied on one side of the fulcrum and the resistance (or load) on the other side, for example, as in a crowbar. As an individual Equus ages, the alveolar tooth length decreases. The data display an exponential increase in force generated as tooth length decreases. The elongation and closure of the root is delayed until the crown is almost entirely worn. When the crown is worn, the mastication forces acting on it are very strong. This is an interesting phenomenon and reinforces our hypothesis that the young tooth’s crown embedded in the alveolus acts as a supporting root. This discovery is based in the observation that fossil ungulates most commonly die at an early age leaving a substantial amount of crown unused. The unused crown is not likely a reserve of tooth crown for a season of hardship because it is rare to find examples of such hardship in the fossil record.